An Overview of the Electron-Transfer Proteins That Activate Alkane Monooxygenase (AlkB) - Williams, Shoshana C.; Austin, Rachel Narehood (Frontiers in Microbiology, 2022)
Alkane-oxidizing enzymes play an important role in the global carbon cycle. Alkane monooxygenase (AlkB) oxidizes most of the medium-chain length alkanes in the environment.1-3 The first AlkB identified was from P. putida GPo1 (initially known as P. oleovorans) in the early 1970s,4,5 and it continues to be the family member about which the most is known. This AlkB is found as part of the OCT-operon, in which all of the key proteins required for growth on alkanes are present.6 The AlkB catalytic cycle requires that the diiron active site be reduced. In P. putida GPo1, electrons originate from NADH and arrive at AlkB via the intermediacy of a flavin reductase and an iron-sulfur protein (a rubredoxin). In this Mini Review, we will review what is known about the canonical arrangement of electron-transfer proteins that activate AlkB and, more importantly, point to several other arrangements that are possible. These other arrangements include the presence of a simpler rubredoxin than what is found in the canonical arrangement, as well as two other classes of AlkBs with fused electron-transfer partners. In one class, a rubredoxin is fused to the hydroxylase and in another less well-explored class, a ferredoxin reductase and a ferredoxin are fused to the hydroxylase (ferr_ferrR_AlkB). We review what is known about the biochemistry of these electron-transfer proteins, speculate on the biological significance of this diversity, and point to key questions for future research.